ANALISIS PELUANG USAHA BENGKEL MOTOR LISTRIK DENGAN KONSEP GREEN TECHNOLOGY DI KOTA DENPASAR - swastika, I Gede Angga Swastika (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This research aims to analyze business opportunities for electric motor workshops with a green technology concept in Denpasar City. The analytical tools used in this research include qualitative descriptive analysis to determine business opportunities and SWOT analysis for business opportunity development strategies. Based on the survey conducted in the field, the potential for a green technology-based electric motor workshop business in Denpasar City is promising. Currently, there is a growing awareness among the public about the importance of environmental conservation to reduce greenhouse gas emissions and air pollution, one of which is by using electric motorcycles. In this concept, an electric motor workshop can be a potential platform for developing a business focused on technology that reduces negative environmental impacts. This will stimulate a high demand for electric motorcycles and ultimately be related to the increasing need for electric motor workshops.